2008
DOI: 10.1108/14717794200800015
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate care: what are service users' experiences of rehabilitation?

Abstract: The Department of Health's introduction of intermediate care recognised the need for rehabilitation following acute hospital care. The importance of rehabilitation was also stressed by a review carried out across England and Wales by District Audit. This article reports a phenomenological study carried out to explore service users' experiences of a 22‐bedded intermediate care service. Face‐to‐face, semi‐structured interviews were conducted with eight service users who were older people, with a further follow‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 9 publications
3
27
0
2
Order By: Relevance
“…Minimal participation in the discharge process was reported in several studies (Almborg et al 2008;Benten and Spalding 2008;Foss and Hofoss 2011;Perry et al 2011;Somme et al 2008). Swinkels and Mitchell (2008) focused on elderly patients' perceptions of effects of delayed transfer into the community, involvement in discharge planning and future community care needs.…”
Section: Participation In Discharge Planningmentioning
confidence: 99%
See 4 more Smart Citations
“…Minimal participation in the discharge process was reported in several studies (Almborg et al 2008;Benten and Spalding 2008;Foss and Hofoss 2011;Perry et al 2011;Somme et al 2008). Swinkels and Mitchell (2008) focused on elderly patients' perceptions of effects of delayed transfer into the community, involvement in discharge planning and future community care needs.…”
Section: Participation In Discharge Planningmentioning
confidence: 99%
“…Information was provided orally. In one study by Benten and Spalding (2008) (Perry et al 2011;Swinkels and Mitchell 2008) documented that some patients were not aware of their own formal discharge plan. One study (Foss and Hofoss 2011) revealed sparsely information to patients about discharge.…”
Section: Informationmentioning
confidence: 99%
See 3 more Smart Citations